An Examination of the Enforcement of Ireland’s Public Health (Alcohol) Act 2018: A Paper Tiger - Frank Houghton; John Lombard (Addicta: The Turkish Journal on Addictions)
Ireland’s Public Health (Alcohol) Act 2018 has been heralded as a crucial step in alcohol control. However, the application of such legislation must necessarily involve recourse to the full means of enforcement and deterrence provided by the Act. This research, which is based on four Freedom of Information (FOI) Act requests, examined data on Environmental Health Service inspections and enforcement actions between 2019 and 2023, as they related to the 2018 Act. Although compliance rates have improved over time, they remain below 86% and appear to be plateauing. It is notable that in four full years of operation, no convic- tions for summary or indictable offences related to the Act were recorded, despite over 1900 inspections reporting non-compliance. More robust enforcement actions are appropriate to promote adherence to the Act. Authorized officers should ensure that all enforcement fully complies with the Act by publishing and maintaining a transparent register of actions taken.